Begonia Inventory Along the Rantau Malam Hiking Trail, TNBBBR, Indonesia - Debora, Siska; Lovadi, Irwan; Gusmalawati, Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Begonia is a herbaceous plant that grows in tropical rainforests from lowland and highland areas. Until now, exploration of Begonia in West Kalimantan is mostly done in lowland areas. Data on Begonia spread in highland areas in West Kalimantan are still limited. The study aims to investigate Begonia types, morphological characteristics, and habitats. The hiking track of the Rantau Malam Resort in Bukit Baka Bukit Raya National Park, Sintang Regency, was the site of this study. The cruising method was used for sampling. The results showed that there were five types of Begonia, namely B. lailana Kiew & Geri, B. mariaensis Rimi & Simun, B. paoana Kiew & S. Julia, B. danumensis F.Y Chong and B. bawangensis Houghes. Four of the five Begonia types grow on soil, while one grows on rocks. Begonia mariaensis is a new record for Indonesia.